2017
DOI: 10.21010/ajtcam.vi15.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Subacute Anti-Inflammatory Activities of Dichloromethane Extract of Cassia Alata (Linn.) Leaves in Wistar Rats

Abstract: Background: In Burkina Faso, leaves of Cassia alata are used in the treatment of several diseases, including inflammation. This study evaluated the anti-inflammatory effects of the dichloromethane extract of Cassia alata leaves (CF-AECal) on different models of inflammation in wistar rats in order to enhance its use in traditional medicine. Materials and Methods: Acute inflammation was induced among rats with 0.1 ml of carrageenan, serotonin, histamine and dextrane 1%. The effects of the CF-AECal 50 mg/kg and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In vitro studies showed that akapulko had antibacterial, 36,44,52,53,54 anti-inflammatory, 55,56 anti-oxidant, 37,40,57,58 hepatoprotective, 59 cardioprotective, 60 anti-tumor 61,62,63 and anti-malarial 64 properties. The most extensively studied property of akapulko was its antifungal ability.…”
Section: In Vitro Studies Confirming the Antifungal Properties Of Senmentioning
confidence: 99%
“…In vitro studies showed that akapulko had antibacterial, 36,44,52,53,54 anti-inflammatory, 55,56 anti-oxidant, 37,40,57,58 hepatoprotective, 59 cardioprotective, 60 anti-tumor 61,62,63 and anti-malarial 64 properties. The most extensively studied property of akapulko was its antifungal ability.…”
Section: In Vitro Studies Confirming the Antifungal Properties Of Senmentioning
confidence: 99%